AI-mediated translation presents two possible futures for academic publishing in a multilingual world. - Tatsuya Amano; Lynne Bowker; Andrew Burton-Jones (PLoS Biology)
As the availability and performance of artificial intelligence for language editing and translation continues to improve, we can imagine a future in which everyone can use their own language to write, assess, and read science. The question is, how can we achieve it?